The Effect of Work Life Balance, Burnout and Workload on Employee Performance at Transportation Service Companies in Bandung City - Pani Nopiani; Umi Narimawati (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2022)
Employees at a transportation service company in the city of Bandung feel that there is no balance between work and personal life, burnout from physical and emotional exhaustion, excessive workloads that must be completed on time and not using time efficiently and effectively. This study aims to determine the effect of work life balance, burnout and workload on employee performance at transportation service companies in Bandung City partially and simultaneously. Research with descriptive, verification and quantitative methods. The sampling technique was saturated sampling by 30 respondents. Data analysis is multiple linear regression with SPSS processing. The results of this study are based on descriptive analysis that work life balance, burnout, workload and employee performance are in fairly good condition. The verification analysis states that there is a significant effect between work life balance, burnout, and workload partially and simultaneously on employee performance at transportation service companies in Bandung City.